2023
DOI: 10.1093/cercor/bhad055
|View full text |Cite
|
Sign up to set email alerts
|

The occipital place area represents visual information about walking, not crawling

Abstract: Recent work has shown that the occipital place area (OPA)—a scene-selective region in adult humans—supports “visually guided navigation” (i.e. moving about the local visual environment and avoiding boundaries/obstacles). But what is the precise role of OPA in visually guided navigation? Considering humans move about their local environments beginning with crawling followed by walking, 1 possibility is that OPA is involved in both modes of locomotion. Another possibility is that OPA is specialized for walking o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
7
3
Order By: Relevance
“…Speci cally, Kamps and colleagues have shown increased response in TOS/OPA during ego-motion vs. static scene presentation (Kamps et al, 2016). Jones et al have also shown that ego-motion (and not other types of movements) enhances TOS/OPA activity when compared to scrambled scenes (Jones et al, 2023). In contrast to these ndings, our tests showed weak-to-no egomotion related activity enhancement in area TOS/OPA.…”
Section: Pigs Is Not Just Another Scene Selective Areacontrasting
confidence: 79%
“…Speci cally, Kamps and colleagues have shown increased response in TOS/OPA during ego-motion vs. static scene presentation (Kamps et al, 2016). Jones et al have also shown that ego-motion (and not other types of movements) enhances TOS/OPA activity when compared to scrambled scenes (Jones et al, 2023). In contrast to these ndings, our tests showed weak-to-no egomotion related activity enhancement in area TOS/OPA.…”
Section: Pigs Is Not Just Another Scene Selective Areacontrasting
confidence: 79%
“…Specifically, Kamps and colleagues have shown increased response in TOS/OPA during ego-motion vs. static scene presentation ( Kamps et al, 2016 ). Jones et al, 2023 have also shown that ego-motion (and not other types of movements) enhances TOS/OPA activity when compared to scrambled scenes. In contrast to these findings, our tests showed weak-to-no ego-motion-related activity enhancement in area TOS/OPA.…”
Section: Discussionmentioning
confidence: 82%
“…While in our study, the coherently and incoherently changing stimuli were refreshed with the same temporal frequency (see ‘Methods’). In the study by Jones et al, 2023 , the response to scrambled scenes was used as a control condition, whereas our stimuli were more equivalent, differing only in the sequence of image presentation. Moreover, these studies used higher levels of spatial smoothing (FWHM = 5 mm) compared to the values we used here during preprocessing.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Kamps and colleagues have shown increased response in TOS/OPA during ego-motion vs. static scene presentation ( Kamps et al, 2016 ). Jones et al have also shown that ego-motion (and not other types of movements) enhances TOS/OPA activity when compared to scrambled scenes ( Jones et al, 2023 ). In contrast to these findings, our tests showed weak-to-no ego-motion related activity enhancement in area TOS/OPA.…”
Section: Discussionmentioning
confidence: 99%